Characterization of 3'-untranslated region of the mouse GDNF gene - Oh-hashi, Kentaro (BioMed Central, 2012)
BACKGROUND: Glial cell line-derived neurotrophic factor (GDNF) is a potent survival factor for many cell types, and its expression is widespread both within and outside of the nervous system. The regulation of GDNF expression has been extensively investigated but is not fully understood. RESULTS: Using a luciferase reporter assay, we identified the role of the 3'-untranslated region (3'-UTR) of the mouse GDNF gene in the regulation of gene expression. We focused on a well-conserved A- and T-rich region (approximately 200 bp in length), which is located approximately 1000 bp downstream of the stop codon in exon 4 of the gene and contains three typical AU-rich elements (AREs), AUUUA. Interestingly, these AREs are well conserved in several GDNF genes. By testing reporter constructs containing various regions and lengths of the 3'-UTR fused to the end of the luciferase gene, we demonstrated that the ARE-induced decrease in luciferase activity correlates with the attenuation of the mRNA stability. Furthermore, we found that several regions around the AREs in the 3'-UTR suppressed the luciferase activity. Moreover, the expression level of the GDNF protein was negligible in C6 glioma cells transfected with the ARE-containing GDNF expression vector. CONCLUSIONS: Our study is the first characterization of the possible role of AREs and other suppressive regions in the 3'-UTR in regulating the amounts of GDNF mRNA in C6 cells.